Quinua, Chenopodium quinua (Willd.) en Colombia: Caracterización de gránulos de almidón nativo de quinua por IR-ATR, MEB, DRX (2015)
This article explores the starch granules contained in grain-seeds of quinoa grown in Colombia, it is also providing information on the characteristics of starch by ATR-IR, SEM and XRD, enabling two aspects, on the one hand, to define the potential of use of starch in different industries, and also aspects of cultivation, harvesting, post-harvest and commercialization of quinoa that is sold in Colombia.